Modern Science and Cosmology (The Implications of the Society's View of God) - Yusuf, Himyari; Wekke, Ismail Suardi; Yudha, Gesit (Opción, 2019)
This study aimed to identify the implications of the society's view of God and Religion via qualitative comparative research method. In result, the conflict between religion and science was caused by the fact that cosmology and metaphysics were narrowly understood from their essential meaning. In Indonesian context, science and religion discourses are still dominated by the philosophers and religionists that most of them do not have adequate background in science. In conclusion, science is considered by a modern society as a god who has the authority to determine a truth so it denies the immaterial truth that comes from God.